Increased Clot Formation in the Absence of Increased Thrombin Generation in Patients with Peripheral Arterial Disease: A Case–Control Study - Kleinegris, Marie-Claire F.; Konings, Joke; Daemen, Jan W.; Henskens, Yvonne; de Laat, Bas; Spronk, Henri M. H.; ten Cate-Hoek, Arina J.; ten Cate, Hugo (Frontiers in Cardiovascular Medicine, 2017)
Background In peripheral arterial disease (PAD), activation of the hemostatic system may contribute to atherosclerosis progression and atherothrombotic events. Objective This case–control study assesses the overall coagulation status in PAD patients by evaluating coagulation markers in combination with thrombin generation potential, whole blood (WB) clot formation, and fibrinolysis. Methods In blood from 40 PAD patients (n = 20 with cardiovascular event within 1 year after initial diagnosis, n = 20 without) and 40 apparently healthy controls, thrombin generation was determined in WB and platelet-poor plasma. Whole blood rotational thromboelastometry (ROTEM) measurements were triggered with tissue factor with/without tissue plasminogen activator. Results We observed increased levels of erythrocyte sedimentation rate, leukocytes, eosinophil granulocytes, vWF antigen, fibrinogen, and D-dimer in PAD patients (p < 0.05). Markers of thrombin generation potential showed no difference between patients and healthy controls. In PAD patients with event compared to patients without, WB-thrombin generation showed a lower thrombin potential when triggered with 0 and 2.5 pM tissue factor. The ROTEM clotting assay showed significantly faster clot formation and increased clot firmness in PAD patients compared to controls. No significant differences were found for parameters of clot degradation. Conclusion There are no significant differences between the thrombin generation profiles of PAD patients and healthy controls. Between PAD patients with and without cardiovascular event, the WB thrombin generation appears to differ. Mechanistically, PAD patients show an increased ability to form a stable clot in WB in comparison to healthy controls. This is most likely due to the increased fibrinogen levels related to the inflammation in atherosclerosis, confirming the importance of the inflammation-coagulation axis.